Maldives : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Maldives. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper focuses on Maldives' Request for Disbursement Under the Rapid Credit Facility. The pandemic is inflicting significant damage, especially on tourism activity, and is expected to result in substantial weakening of the Maldives' gross domestic product growth, balance of payments and the fiscal position. The government of the Maldives acted quickly to put in place containment measures and is seeking support from the international community for its crisis response plan. The authorities have responded quickly to the coronavirus disease 2019 outbreak, including specific travel restrictions and subsequently more comprehensive travel measures. They also put together a set of measures to alleviate its social and economic fallout. The temporary fiscal accommodation is appropriate. The authorities will reprioritize and cut capital expenditures, redirecting funds as needed to combat the pandemic and provide temporary and well-targeted support to the most vulnerable households and businesses, while maintaining high standards of transparency and governance. The authorities remain committed to fiscal and debt sustainability over the medium term. They intend to achieve a balanced fiscal adjustment based on the reduction of capital spending to historical averages, recurrent expenditure discipline, and revenue mobilization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet